PENINGKATAN PENGETAHUAN DAN KETERAMPILAN KELOMPOK TANI MELALUI PEMANFAATAN PUPUK ORGANIK BOKASHI PADA BUDIDAYA TANAMAN DURIAN DI DESA ANGGOTOA KABUPATEN KONAWE - Suharjo Suharjo; Ulyasniati Ulyasniati; Milawati Saranani (LPPM Institut Pendidikan Nusantara Global, 2026)
This community service activity aimed to improve the knowledge and skills of the community in utilizing bokashi organic fertilizer for durian cultivation in Anggotoa Village, Wawotobi District, Konawe Regency. The main problem faced by the community was the limited understanding of yard land management and the use of organic fertilizers in horticultural cultivation, especially durian plants. The implementation methods included field observation, socialization, discussion, and evaluation through questionnaires. The targets of the activity were farmer groups and housewives in Anggotoa Village. The results showed that participants had a good understanding of the materials presented. Around 74–85% of participants stated that they understood the socialization materials, while 14–25% stated that they highly understood the materials. The use of bokashi fertilizer increased community awareness regarding the use of organic materials to improve soil fertility and durian productivity. This activity was expected to become an initial step in developing environmentally friendly agriculture based on local resource utilization.